Evaluasi Efisiensi dan Profitabilitas Asuransi Syariah Melalui Analisis Laporan Keuangan - Dewi Widya Ningrum; Isma Fauziyah; Neti Widianti (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
In the literature study related to evaluating the efficiency and profitability of Islamic insurance through financial statement analysis, previous studies highlighted various methods and approaches used to measure the performance of Islamic insurance companies. Financial statement analysis is the main focus in identifying factors that affect the operational efficiency and profitability of Islamic insurance companies. Some studies have used traditional financial ratios such as solvency, liquidity, and profitability ratios to evaluate the performance of Islamic insurance. However, due to the unique characteristics of Islamic insurance, studies have also proposed the development of specific metrics that take into account sharia principles, such as sharia compliance ratios and fairness ratios. In addition, non-financial approaches such as technical efficiency and allocative efficiency analysis have also been used to evaluate the operational efficiency of Islamic insurance. This research shows that factors such as scale of operations, business diversification, and managerial efficiency can contribute to the efficiency performance and profitability of Islamic insurance companies. Although there have been many studies conducted in this domain, there is still a need for more in-depth follow-up research to better understand the factors that influence the efficiency and profitability of Islamic insurance. With a better understanding of the performance of Islamic insurance companies, regulators and practitioners can develop more effective strategies to improve the stability and growth of this industry.